Dermoscopy in pediatric dermatosis - Gopalsing Rameshsing Rajput; Manas Chatterjee; Ruchi Hemdani (Apollo Medicine)
Introduction: Paediatric dermatoses differ from adult dermatoses with respect to clinical presentation, treatment and prognosis. These can be transitory, chronic and recurrent. The chronic dermatoses are associated with significant morbidity and psychological impact. Diagnosing these conditions is at times a challenge and the use of dermoscope aids it. Dermoscopy in paediatric population has unique advantage as it poses neither physical discomfort nor emotional stress. Therefore this review was attempted to highlight the salient dermoscopy features of common dermatoses in paediatric age group. Methods: A systematic literature search using PubMed and Google scholar databases for English language articles published upto the end of May 2019 was done for paediatric dermatoses and dermoscopy. Relevant studies were included. Cross references from each study are also included. Results: The common dermoscopy features of atopic dermatitis”, “lichen planus”, “psoriasis”, “paediatric dermatoses”, “keratosis pilaris”, “impetigo”, “pityriasis rosea”, “pityriasis versicolor”, “granuloma annulare”, “vitiligo”, “hypomelanoses of Ito”, “nevus achromicus”, “molluscum contagiosum”, “verrucae”, “lentigenes”, “freckles”, “capitis”, “pediculosis”, “alopecia areata”, “linear porokeratosis”, “lichen sclerosus et atrophicus”, “pityriasis alba”, “acanthosis nigricans”, “hand foot mouth”, “seborrheic dermatitis” and “prurigo nodularis identified from literature search were included. Conclusion: Paediatric dermatoses are unique in presentation as they might overlap to some extent. The diagnosis of these conditions is complicated by the fact that a biopsy may not always be possible since children are not co-operative and more importantly, parents are reluctant to subject their children to an invasive procedure. It is in this perspective that dermoscopy assumes greater importance in pediatric dermatology as compared to that in adults.